Measurement of productivity and efficiency : theory and practice - Sickles, Robin C.; Zelenyuk, Valentin (Cambridge : Cambridge University Press, 2019)
Methods and perspectives to model and measure productivity and efficiency have made a number of important advances in the last decade. Using the standard and innovative formulations of the theory and practice of efficiency and productivity measurement, Robin C. Sickles and Valentin Zelenyuk provide a comprehensive approach to productivity and efficiency analysis, covering its theoretical underpinnings and its empirical implementation, paying particular attention to the implications of neoclassical economic theory. A distinct feature of the book is that it presents a wide array of theoretical and empirical methods utilized by researchers and practitioners who study productivity issues. An accompanying website includes methods, programming codes that can be used with widely available software like MATLAB® and R, and test data for many of the productivity and efficiency estimators discussed in the book. It will be valuable to upper-level undergraduates, graduate students, and professionals.
Production theory : primal approach -- Production theory: dual approach -- Efficiency measurement -- Productivity indexes: Part 1 -- Aggregation -- Functional forms -- Productivity indexes: part 2 -- Envelopment-type estimators -- Statistical analysis for DEA & FDH: Part 1 -- Statistical analysis for DEA & FDH: Part 2 -- Cross-sectional stochastic frontiers -- SF models-first generation panel approaches -- SF models-second generation approaches -- Endogeneity -- Dynamic models -- Shape restrictions and model averaging -- Measurement, KLEMS, and other data -- Afterword -- Bibliography.
Title from publisher's bibliographic system (viewed on 13 Mar 2019).
Keywords: Labor productivity -- Measurement; Industrial efficiency -- Measurement -- Mathematical models; Performance -- Management